PERAN PERILAKU KOMUNIKASI INTERPERSONAL GENERASI Z DALAM PEMANFAATAN MEDIA DIGITAL - Lutfiah, Alifya Qultsum; Rahmadianti, Destya; Febrianto, Abi Sopyan (Jurnal MANAJERIAL, 2024)
This article explores the role of interpersonal communication in the context of Generation Z (Gen Z), a generation born after 1995 that has grown up in the digital age. Gen Z, the first generation to come of age in the era of digital technology, exhibits varied preferences for digital media depending on the context. However, they still view interpersonal communication as a crucial element in socializing. Utilizing qualitative methods and drawing from literature in journals, books, and previous research, this study delves into the shifts in Gen Z's interpersonal communication behavior in the digital media landscape. The findings indicate that Gen Z actively engages in interpersonal communication through social media and digital platforms for interaction, sharing creative content, and building social relationships. This has resulted in a shift from active to passive communication behaviors, an increased expression of self through digital media, a changed perspective on face-to-face communication, and a decrease in in-person communication. This article provides insights into the role of interpersonal communication in Generation Z, highlighting changes in interpersonal communication behaviors in the digital media era.